GAYA HIDUP INSTAGRAM DAN MINUM KOPI : KAJIAN REPRESENTASI DIRI, KONSUMERISME DAN HIBRIDITAS - Dhyani Widiyanti Hendranto (Serat Rupa: Journal of Design, 2022)
The “Instagram lifestyle” is a lifestyle that represents eagerness to document a person’s daily life and then having it displayed on Instagram so that it can be known by the public at large. Popular content that is frequently displayed are moments of coffee drinking. Such coffee drinking moments which are displayed on Instagram are interesting subjects to be studied due to their connection to representations of a particular self-identity associated with a culture of consumerism. By using visual analysis in conjunction with literature research - especially those related to self-identity, consumerism, and post-colonialism culture - the study aims to see the relationship between coffee drinking activities, visual appearances on Instagram and their associated broader meanings. The results of the study show that there are attempts to form self-identities that are expressed in the virtual space through display of images accompanied by text and other supporting information (geographical tagging, captions, hashtags, etc.). Consumerism culture is also evident in the relationship between "free time" and the act of "buying". Expressions of enjoying free time can be observed in poses and gestures such as holding cigarettes, laughing, and relaxing. While the culture of consumerism can be noted from how the coffee drinkers or content creators are marketing a particular product. Finally, hybridity befalls, the "colonizers" renders colonialism more "friendly" through local and cultural images. Meanwhile for the “colonized”, the documentation of “coffee drinking” on Instagram will make both the activity and the coffee itself widely known not only nationally but also in internationally.